RNA-Seq Transcriptome Analysis Provides Candidate Genes for Resistance to Tomato Leaf Curl New Delhi Virus in Melon - Sáez, Cristina; Flores-León, Alejandro; Montero-Pau, Javier; Sifres, Alicia; Dhillon, Narinder P. S.; López, Carmelo; Picó, Belén (Frontiers in Plant Science, 2022)
Tomato leaf curl New Delhi virus (ToLCNDV) emerged in the Mediterranean Basin in 2012 as the first DNA bipartite begomovirus (Geminiviridae family) causing severe yield and economic losses in cucurbit crops. A major resistance locus was identified in the wild melon accession WM-7 (Cucumis melo kachri group), but the mechanisms involved in the resistant response remained unknown. In this work, we used RNA-sequencing to identify candidate genes that are differentially expressed in the course of ToLCNDV infection and could contribute to resistance. Transcriptomes of the resistant WM-7 genotype and the susceptible cultivar Piñonet Piel de Sapo (PS) (C. melo ibericus group) in ToLCNDV and mock inoculated plants were compared, at four time points during infection (0, 3, 6, and 12 days post inoculation). Different gene expression patterns were observed over time in the resistant and susceptible genotypes in comparison to their respective controls. Differentially expressed genes (DEGs) in ToLCNDV infected plants were classified using GO terms, and genes of the categories transcription, DNA replication and helicase activity, were down-regulated in WM-7, but up-regulated in PS, suggesting that reduced activity of these functions reduces ToLCNDV replication and intercellular spread and thereby contributes to resistance. DEGs involved in the jasmonic acid signaling pathway, photosynthesis, RNA silencing, transmembrane and sugar transporters entail adverse consequences for systemic infection in the resistance genotype, while lead to susceptibility in PS. The expression levels of selected candidate genes were validated by qRT-PCR to corroborate their differential expression upon ToLCNDV infection in resistant and susceptible melon. The obtained results pinpoint cellular functions and candidate genes that are differentially expressed in a resistant and susceptible melon line in response to ToLCNDV, an information of great relevance for breeding ToLCNDV resistant melon cultivars.